Beyond right and left : democratic elitism in Mosca and Gramsci - Finocchiaro, Maurice A., 1942- (Yale University Press, 1999)
Two Italian writers, Gaetano Mosca and Antonio Gramsci, have been very influential in twentieth-century political thought, the first cast as a thoroughgoing conservative, the second as the model of a humanistic Marxist. The author of this provocative book, the first systematic study of the connection between the two men, maintains that they are closer to each other than is commonly supposed-that they in fact belong to the same political tradition of democratic elitism. Maurice A. Finocchiaro argues that Gramsci's political theory is a constructive critique of Mosca's and that the key common element is the attempt to combine democracy and elitism in a theoretical system that defines them not as opposite but as compatible and interdependent. Finocchiaro finds that a critical examination of the major works of the two men demonstrates their shared belief in the viability of democratic elitism and undermines the importance of the distinction between right and left.
Keywords: Mosca, Gaetano, -- 1858-1941 -- Contributions in political science.; Gramsci, Antonio, -- 1891-1937 -- Contributions in political science.; Gramsci, Antonio, -- 1891-1937; Mosca, Gaetano, -- 1858-1941; Democracy.; Elite (Social sciences); Right and left (Political science); Élite (Sciences sociales); POLITICAL SCIENCE -- Political Ideologies -- General.; POLITICAL SCIENCE -- History & Theory.; Democracy; Political science; Democratie.; Elites.; Theorievorming.